The role of transport infrastructure on foreign direct investment in Malaysia - Nor Asma Ahmad; Azila Jaini; Zaminor Zamzamir@Zamzamin; Yuhanis Mohamed Noor (Faculty of Entrepreneurship and Business,UMK, 2015)
Foreign Direct Investment (FDI) is an important contributor to the development and the transformation of the Malaysian economy, particularly in establishing new industries, enhancing production capacity, employment, trade and technological capability. This study investigates the impact of tansport infrastructure on FDI in Malaysia from 1980 to 2013. Time series Malaysian data is used to capture the role of infrastructure on FDI through ARDL method. There were four hypothesized indicators in this study; air transport and road transport along with the common variables to measure FDI. The results revealed that it was evident that both infrastructure variables had positive impact on FDI in Malaysia. The findings suggest that the improvement of infrastructure though lowered transportation costs helped to increase competitiveness in attracting FDI.